Controlled delivery of ciprofloxacin and ivacaftor via sinus stent in a preclinical model of Pseudomonas sinusitis. Issue 4 (23rd December 2019) - Lim, Dong‐Jin; McCormick, Justin; Skinner, Daniel; Zhang, Shaoyan; Elder, Jeffrey B.; McLemore, John G.; Allen, Mark; West, John Martin; Grayson, Jessica W.; Rowe, Steven M.; Woodworth, Bradford A.; Cho, Do‐Yeon
Abstract : Background: Pseudomonas aeruginosa is common in chronic rhinosinusitus (CRS) and frequently resistant to antibiotic treatment. We recently described the ciprofloxacin and ivacaftor‒releasing biodegradable sinus stent (CISS)―a drug‐delivery system that administers ciprofloxacin and the mucociliary activator (ivacaftor) at high local concentrations with prolonged mucosal contact time and sustained delivery. The objective of this study is to evaluate the efficacy of the CISS in a rabbit model of P aeruginosa (PAO1 strain) sinusitis. Methods: Ciprofloxacin/ivacaftor (double layer) was coated on biodegradable poly‐D/L‐lactic acid (PLLA). A total of 10 sinus stents (5 bare PLLA stent controls, 5 CISSs) were placed unilaterally in rabbit maxillary sinuses via dorsal sinusotomy after inducing infection for 1 week with PAO1. Animals were assessed 3 weeks after stent insertion with sinus culture, nasal endoscopy, computed tomography scan, histopathology, and in‐vivo sinus potential difference (SPD) assay. Results: Rabbits treated with CISS had significant reductions in computed tomography (∆ Kerschner scale: control, 0.55 ± 0.92; CISS, −5.92 ± 1.69; p = 0.024) and endoscopy (control, 4.0 ± 0.0; CISS, 1.875 ± 0.74; p = 0.003) scores. A 2‐log reduction of PAO1 was observed (control, −2.14 ± 0.77; CISS, 1.84 ± 1.52; p = 0.047). SPD revealed significantly increased Cl − transport in the CISS group compared with the control group (Cl − ‐free + forskolin ΔPD: control, −4.23 ± 1.04 mV; CISS, −18.36 ± 6.31 mV; p = 0.026). Finally, marked improvements were noted in the histology of the mucosa and submucosa in treated animals. Conclusion: The CISS had robust clinical efficacy in treating P aeruginosa rabbit sinusitis. The innovative design of double‐layered drug coating on the surface of the biodegradable stent may provide therapeutic advantages over current treatment strategies for P aeruginosa sinusitis.